Pendekatan Integralistik sebagai Media Alternatif Inovasi Pendidikan Islam di Era Milenial - Hasanah, Nur Zaytun; Zakly, Dhiko Saifuddin (STAI Auliaurrasyidin Tembilahan, 2021)
In the current millennial era, many young Muslim generations are exposed to the millennial effect, which has an impact on emerging behavior. The purpose of this study was to describe an integrated approach as an alternative medium for Islamic education innovation. This research is a descriptive qualitative approach. Data collection techniques used were observation, documentation, and interview. The data were analyzed using Miles Huberman and Saldana's stages of data collection, data condensation, data presentation, and conclusion drawing. The results showed that the integrated approach implemented at SMP IT Salman Al-Farizi Yogyakarta was able to be an alternative media for Islamic education innovation in the millennial era. This integrated approach makes the Islamic faith as its foundation, it also enables teachers to create students who have Islamic personalities, smart, and skillful in mastering science and technology.